1993
DOI: 10.1210/jcem.77.6.7505289
|View full text |Cite
|
Sign up to set email alerts
|

The composition and distribution of insulin-like growth factors (IGFs) and IGF-binding proteins (IGFBPs) in the serum of growth hormone receptor-deficient patients: effects of IGF-I therapy on IGFBP-3.

Abstract: We have previously reported that adult GH receptor-deficient (GHRD) patients treated subcutaneously with recombinant human insulin-like growth factor (IGF)-I have increased serum IGF-I levels and decreased IGF-II levels, whereas IGF-binding protein-3 (IGFBP-3) levels were unchanged. To further investigate the effects of IGF-I administration upon the IGF-IGFBP axis in GHRD, we have examined: 1) the molecular distribution of IGF-I and IGF-II among the IGFBPs; 2) the composition and distribution of the IGFBPs, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…After birth, the patient grew poorly and had low BMD, confirming the central role of IGF-I in postnatal growth, as suggested in the somatomedin hypothesis (Salmon and Daughaday, 1957). Interestingly, the patient's serum IGFBP-3 and ALS concentrations were normal-findings in support of recent studies showing that these peptides are controlled independently of IGF-I in humans (Gargosky et al, 1993;Hardouin et al, 1989;Zapf et al, 1989;Baxter, 1990). However, a similar skeletal phenotype was recently reported for a human mutation in ALS, the major carrier protein for IGFBP-3 and IGF-I (Domene et al, 2004).…”
Section: Human Studies Of Human Igf-i Polymorphisms and Bone Acquisitionsupporting
confidence: 84%
“…After birth, the patient grew poorly and had low BMD, confirming the central role of IGF-I in postnatal growth, as suggested in the somatomedin hypothesis (Salmon and Daughaday, 1957). Interestingly, the patient's serum IGFBP-3 and ALS concentrations were normal-findings in support of recent studies showing that these peptides are controlled independently of IGF-I in humans (Gargosky et al, 1993;Hardouin et al, 1989;Zapf et al, 1989;Baxter, 1990). However, a similar skeletal phenotype was recently reported for a human mutation in ALS, the major carrier protein for IGFBP-3 and IGF-I (Domene et al, 2004).…”
Section: Human Studies Of Human Igf-i Polymorphisms and Bone Acquisitionsupporting
confidence: 84%
“…An indirect response to GH has also been investigated by Chin et al (1994) who reported that GH receptor mRNA was absent from IGFBP-3 expressing cells in the liver. However, studies in man are more equivocal; Gargosky et al (1993) reported an inability of IGF-I to increase circulating IGFBP-3 concentrations in GH receptor-deficient patients and Kupfer et al (1993) observed a decline in IGFBP-3 and ALS concentrations in response to IGF-I in calorically-restncted normal adults. These discrepancies can be explained in part by consider¬ ation of IGFBP-3 stability, the half-life of IGFBP-3 being longer when in the ternary than binary complex (Dai & Baxter 1994).…”
Section: Discussionmentioning
confidence: 99%
“…1986) but it is not clear whether this is due to the primary GH deficiency or to the subsequent lack of IGF-I. Studies in which GH or IGF-I have been administered to humans and rats have not yielded consist¬ ent changes in blood IGFBP-3 concentrations (Gargosky et al 1993). It is therefore important to identify the major source(s) of blood IGFBP-3 and to characterize key factors regulating its synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IGFBP-3 was measured by an immunoradiometric assay (IRMA) (Diagnostic System Laboratories Inc., Webster, TX, USA), and ALS by RIA (Bioclone Australia, Marrickville, Australia). In order to determine the distribution of IGFBP-3 in the 150 kDa ternary complex and the non-ternary complex bound fraction, 200 lL of serum from each patient/control was exposed to size-exclusion chromatography at neutral pH as previously described [19], followed by determination of the IGFBP profile by Western ligand blotting (WLB) [20,21], and finally measurement of the IGFBP-3 concentration by IRMA as described above. The column which was used for size-exclusion chromatography was calibrated with proteins of known molecular weight (thyroglobulin (670 kDa), gamma-globulin (158 kDa), ovalbumin (44 kDa), myoglobin (17 kDa), and cyanocobalamin (1.4 kDa); all from Bio-Rad, Melville; NY, USA).…”
Section: Assaysmentioning
confidence: 99%